ASSESSMENT OF HARMFUL SUBSTANCES DISCHARGE IN ENVIRONMENT FROM SOURCES OF FOUNDRY SHOPS - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия)
Sources of harmful substances discharge from sources of casting houses are given. Distribution of harmful substances discharge into atmosphere by areas of casting houses and casting houses with various types of production is given.